Eco-Friendly Biochar-Chitosan Coating for Controlled Nitrogen-Fe Release from Slow-Release Fertilizers - Martasiana Karbeka (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
The development of slow-release fertilizers (SRFs) has gained increasing attention as an efficient approach to enhance nutrient utilization while minimizing nutrient losses and environmental impacts. In this study, biochar–chitosan composites were employed as encapsulating materials for urea and Fe to produce SRF beads. The beads were synthesized through ionic gelation in NaOH solution, followed by swelling tests and structural characterization using Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). The swelling analysis demonstrated that the most effective formulation was obtained from the composition containing 3 g of biochar and 3 g of urea, achieving the highest swelling capacity of 92% after 48 h. This result indicates that the biochar–chitosan matrix provides sufficient porosity and water affinity to support nutrient retention and release. FTIR spectra confirmed the presence of characteristic functional groups of biochar, chitosan, urea, and Fe, verifying the successful incorporation of all components into the composite beads. Furthermore, XRD analysis revealed a predominantly amorphous structure, as evidenced by broad peaks in the 2theta range of 20°–60°. However, sharp crystalline peaks were also observed at 2theta approximately 29.1° and 33.9°, corresponding to urea, and at 2theta approximately 40°, attributed to crystalline phases of urea and Fe. These results suggest that the structural configuration of the beads combines both amorphous and crystalline phases, which may contribute to controlled nutrient release behavior. Overall, the findings demonstrate that biochar–chitosan encapsulation is a promising strategy for developing efficient SRFs with enhanced swelling properties and structural stability, offering potential for sustainable agricultural applications.